Strategies for Low-Temperature Liquid Organic Hydrogen Carrier Dehydrogenation - Müller, Karsten; Skeledzic, Tanja; Wasserscheid, Peter (Energy & Fuels, 2021)
Liquid organic hydrogen carriers (LOHCs) store hydrogen by covalent bonds in a safe and dense manner. Recovery of hydrogen is realized by an endothermal dehydrogenation reaction. Theoretically, its heat demand could be covered by waste heat, e.g., from a fuel cell. However, to facilitate this, it is crucial to increase the temperature level of polymer electrolyte membrane fuel cells and lower the temperature level of the dehydrogenation reaction. In this study, strategies for releasing hydrogen from LOHCs at low temperatures are presented and evaluated. Thereby, the focus is on approaches for overcoming limitations by the reaction equilibrium. We see three main options: (i) dehydrogenation at a low pressure, (ii) dilution of hydrogen with an inert gas, and (iii) reactive distillation. These options are examined, particularly regarding their suitability for integrating waste heat, e.g., from fuel cells. Low-pressure dehydrogenation and reactive distillation show the highest potential for realizing efficient low-Temperature hydrogen release.
CRIS-Team Scopus Importer:2021-07-02